(untitled) (Global Journal of Science Frontier Research, 2016)
The high cost of readymade media like Potato Dextrose Agar, Nutrient agar, Peptone yeast Extract agar and media alike has deprived the use of these in laboratories with low facilities. Legume seeds and products have been found to be a very good protein source. The present study deals with the feasibility of using soy flour as an alternative culture media to grow yeasts. Soy flour has several functional properties other than its high protein content which has been reported as 50%. As the starch content is very low it has a higher dissolving property and it solidifies easily due to its gelling ability. Therefore soy flour can serve as a good nutrient source as well as to replace agar to some extent due to its solidifying property. It was found in this study that soy flour had shown to be a simple, cheap source which can replace peptone in the conventional medium.